Exploration and Exploitation of Oil and Gas Resources in Marine Areas: Development of Russian Legislation in the Light of Changes in Global Politics - O. V. Glikman (Сравнительная политика, 2024)
Legal regulation of exploration and exploitation of oil and gas resources in marine areas, which are subject to the sovereignty, sovereign rights and jurisdiction of the Russian Federation, is of great practical importance for our country, Russian legal entities and individuals. This is confirmed by the Strategy for the Development of Maritime Activities in the Russian Federation until 2030, the Energy Strategy of the Russian Federation for the period until 2035 and the Maritime Doctrine of the Russian Federation, which were adopted in 2019 - 2022. These issues are no less important for foreign entities in connection with their participation in oil and gas marine projects in these territories.The scientific significance of the study is related to the development of International Energy Law, a significant amount of the rules of which are applicable to oil and gas activities in marine areas. The purpose of the study is to comprehensively analyze the development of legal norms of the Russian Federation governing the exploration and exploitation of oil and gas resources in marine areas, which are subject to the sovereignty, sovereign rights and jurisdiction of the Russian Federation, in the period 2014 - 2023, as well as identifying trends in their development in connection with measures taken by unfriendly states against Russia, Russian legal entities and individuals. The objectives of the study include identifying and analyzing trends in the development of legislation of the Russian Federation governing the exploration, exploitation and transportation of oil and gas resources in the specified marine areas, the interconnection of legislative innovations with changes in world politics and international legal problems that arose during this period.The methodological basis of the study is comparative legal and formal legal. The article identifies and analyzes certain trends in the development of legislation of the Russian Federation related to the restriction of the rights of foreign entities in the implementation of subsoil use in offshore subsoil areas of federal significance, the regulation of artificial islands, installations and structures, as well as support for the Russian flag and the domestic manufacturer of sea vessels within the framework of oil and gas activities in the specified marine areas. The author concludes that it is necessary to take timely legislative measures and an integrated approach to the legislative regulation of the issues under consideration.